1979
DOI: 10.3181/00379727-161-40496
|View full text |Cite
|
Sign up to set email alerts
|

Response of Mineralocorticoid Hypertensive Animals to an Angiotensin I Converting Enzyme Inhibitor

Abstract: The recent development of angiotensin I converting enzyme inhibitors has made possible their use in delineating the role of the renin-angiotensin system in different types of hypertension (1). These inhibitors also block agents responsible for kinin destruction (2). Therefore, blood pressure changes due to converting enzyme inhibitors could be due to either inhibition of angiotension I1 formation or increased plasma kinin levels.Bengis et al. administered the angiotensin I converting enzyme inhibitor SQ-14,225… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1980
1980
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 4 publications
1
7
1
Order By: Relevance
“…8 Furthermore, chronic captopril infusion has no effect on either arterial pressure or renal function in circumstances in which endogenous Ang II formation is suppressed to undetectable levels, as occurs with high sodium intake, deoxycorticosterone acetate hypertension, or chronic Ang II hypertension. 34 ' 35 Therefore, the present findings and the results from other chronic studies support the contention that the major effects of captopril on renal function in the present study were mediated via blockade of Ang II formation.…”
supporting
confidence: 80%
“…8 Furthermore, chronic captopril infusion has no effect on either arterial pressure or renal function in circumstances in which endogenous Ang II formation is suppressed to undetectable levels, as occurs with high sodium intake, deoxycorticosterone acetate hypertension, or chronic Ang II hypertension. 34 ' 35 Therefore, the present findings and the results from other chronic studies support the contention that the major effects of captopril on renal function in the present study were mediated via blockade of Ang II formation.…”
supporting
confidence: 80%
“…Reports of the effect of captopril on blood pressure in DOC-salt hypertensive rats area conflicting. 23 ' 24 In the present study, captopril had no effect on blood pressure in DOC-salt hypertensive rats, even though the arterial plasma level of kinins was increased relative to the values in hypertensive rats without captopril treatment. Concerning this point, it has been reported that blood pressure does not fall in intact rats receiving bradykinin infusion until the arterial blood kinin concentration greatly exceeds the basal kinin level.…”
Section: Discussioncontrasting
confidence: 57%
“…SBP, heart rate, and body weight were measured 3 days before drug treatment was begun and at weeks 2,4,6,8,12, and 20 during drug administration. The water intake was estimated at week 16 during drug administration.…”
Section: Drug Treatment Regimen and Measurement Of Blood Pressurementioning
confidence: 99%
“…20 Endothelial cells were removed by rubbing the inner surface of aortic tissue with a cotton stick for 1 minute. The aortic strip was suspended in an organ bath containing 30 ml KHS maintained at 36.5±0.5° C and aerated with a 5% CO 2 Isometric tension of the aorta was measured with a force-displacement transducer (TB-612T, Nihonkohden, Tokyo, Japan) connected to a carrier amplifier (AP-601G, Nihonkohden) and was recorded on a thermal-pen-writing recorder (RJG-4128, Nihonkohden).…”
Section: Experimental Protocol With the Isolated Aortamentioning
confidence: 99%